Disruptive Innovation and Business Development, A Bibliometric Study - Muhammad Taufan (SOSIOEDUKASI, 2026)
This study examines the effects and expansion of disruptive technologies across several sectors, indicating a rise in research efforts and academic fascination. Disruptive innovations, which are distinguished by their unique characteristics, cost-effective methods, and ability to replace dominant market leaders, have a substantial impact on transforming corporate environments. The study emphasizes the importance of contextual elements, such as governmental regulations, technological frameworks, and socio-economic circumstances, in either enabling or impeding these advancements. The findings demonstrate that disruptive technologies frequently bring about simplicity and affordability, specifically targeting market groups that have been neglected and causing substantial changes within the industry. The study also highlights the necessity for ongoing research to investigate the intricacies of disruptive technologies, devise novel research approaches, and tackle existing gaps in knowledge. The results of this study provide valuable information for company executives to predict market changes and adjust their strategy accordingly. Additionally, politicians can use these insights to establish settings that promote innovation. This study enhances the overall discussion on competitive advantage and industrial transformation by furthering the understanding of disruptive technologies.